2020
DOI: 10.3389/fbioe.2020.00036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enzyme Loading and Immobilization Conditions on the Catalytic Features of Lipase From Pseudomonas fluorescens Immobilized on Octyl-Agarose Beads

Abstract: The lipase from Pseudomonas fluorescens (PFL) has been immobilized on octyl-agarose beads under 16 different conditions (varying pH, ionic strength, buffer, adding some additives) at two different loadings, 1 and 60 mg of enzyme/g of support with the objective of check if this can alter the biocatalyst features. The activity of the biocatalysts versus p-nitrophenyl butyrate and triacetin and their thermal stability were studied. The different immobilization conditions produced biocatalysts with very different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 83 publications
0
56
0
Order By: Relevance
“…Additionally, the existence of functional amino and hydroxyl groups makes it susceptible to chemical treatments [10]. One of the important types of immobilization methods is cross-linking in which the amino groups of the enzyme are connected covalently to the functional groups of the cross-linker such as glutaraldehyde to create a new bond for increasing the stability of the enzyme [11][12][13]. Using glutaraldehyde as a cross-linking agent increases the enzyme chance for successful reuse and gives it extraordinary advantages for a wide range of industries like food, fuel, and chemical as well as pharmaceuticals [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the existence of functional amino and hydroxyl groups makes it susceptible to chemical treatments [10]. One of the important types of immobilization methods is cross-linking in which the amino groups of the enzyme are connected covalently to the functional groups of the cross-linker such as glutaraldehyde to create a new bond for increasing the stability of the enzyme [11][12][13]. Using glutaraldehyde as a cross-linking agent increases the enzyme chance for successful reuse and gives it extraordinary advantages for a wide range of industries like food, fuel, and chemical as well as pharmaceuticals [14].…”
Section: Introductionmentioning
confidence: 99%
“…The immobilized enzyme derivatives were compared with the commercial lipase B from Candida antarctica (CALB), immobilized on octyl Sepharose . Very low enzyme loadings of the supports were employed to prevent substrate diffusional limitations [65][66][67][68][69] and to prevent intermolecular enzyme-enzyme interactions that could alter the final performance of the biocatalysts [70,71].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of lipases, all these advantages may be obtained by a very simple immobilization strategy. Using lipases, the best protocol to have an improved biocatalyst is just a simple physical adsorption of the enzyme on the support: the interfacial activation of the lipases versus support Although lipase immobilization on hydrophobic supports may be achieved under a wide range of conditions, it has been recently shown that the immobilization medium conditions may greatly alter the properties of the immobilized lipases, at least when using some lipases [366][367][368]. This may be considered as an advantage, as it permits the modulation of the enzyme properties using a single immobilization support [61], or as a problem, as this means that changes in the immobilization medium composition may produce biocatalysts with different catalytic properties (activity, specificity, stability), and this may be in some instances hard to control (Figure 19).…”
Section: Use Of Individually Immobilized Lipasesmentioning
confidence: 99%
“…It has been widely showed that changes in the immobilization protocol or the physical or chemical modification of the immobilized lipases may greatly alter the enzyme features [61]. Using the same immobilization mechanism, e.g., the interfacial activation of the lipase versus hydrophobic support surfaces [81,360], it has been shown that the change of the support features greatly affects the final enzyme specificity, activity and stability [425][426][427]-even immobilization of the same enzyme using the same hydrophobic support, but just changing the immobilization conditions gives very different enzyme properties [366][367][368] (Figure 19). In fact, it has been recently shown that the lipase from T. lanuginosus immobilized on a hydrophobic support under certain conditions was a strict 1,3 selective enzyme, being unable to hydrolyze 2-monoglycerides, while the enzyme immobilized under other conditions can hydrolyze 2-monoglycerides, and that also depended on the immobilization support [428,429].…”
Section: Use Of Mixtures Of the Same Lipase Immobilized Following Different Protocols: A Special Combilipasementioning
confidence: 99%